Analisis Peraturan Bupati Nias Nomor 24 Tahun 2020 Dalam Penanganan Stunting Studi Kasus: Puskesmas Kecamatan Hiliduho - Zalukhu, Iman Setiawan Anugrah; Manalu, Dimpos; Pasaribu, Vera A.R. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
Stunting handling is the Sustainable Development Goals (SDGs) target to overcome malnutrition and achieve food security in 2030. Stunting is a failure to grow on toddlers due to chronic malnutrition, especially in 1,000 First Life Day (HPK), which has an impact on child's growth and cognitive appearance. In 2023, Hiliduho District has a quite high stunting rate, and Hiliduho District Health Center plays a role as the forefront of his handling. This study aims to analyze the Regent Regulation Number 24 of 2020 related to stunting in realizing SDGs, identifying obstacles, and steps to overcome them. Research methods are qualitative with the study approach through interviews and documentation. The results show that the Hiliduho Health Center carries stunting management based on six service dimensions: safety, effectiveness, patient focus, time accuracy, efficiency and equality. Prevention involves specific and sensitive interventions to meet the needs of mothers and children. Stunting, Sustainable Development Goals (SDGs), Regent Regulation, Health Center